Nursing Beyond Classrooms: Clinical Simulation Insights - Ms. Ritika; Ms. Shephali; Ms. Anjali Chauhan; Ms. Nikita; Mr. Naveen (The Bioscan, 2025)
Introduction: The goal of simulation-based education is to "replace or magnify real experience with guided encounters." A training method called educational simulation involves putting participants in situations where they must actively solve problems in order to assess their knowledge and proficiency levels. Through a realistic, immersive experience, simulation-based learning offers students real-world insights into a subject. Objective: To analyze the knowledge and satisfaction level of Simulation based learning. Materials and Methods: The descriptive study includes 100 students of BSc nursing from SGT University. The sample were selected using random sampling technique .Pre Test and Post Test was done to know the effectiveness of clinical simulation. Data was collected using structured questionnaire that covered demographic factor such as: age in years, area of residence, qualification, previous knowledge regarding simulation based learning, experience of simulation, knowledge regarding clinical simulation and satisfaction among students regarding clinical simulation. Results: Among nursing students, the majority of participants in the pre-test – 54 (54%) – were developing 37 (37%) were novices, and 9 (9%) were experts in clinical simulation. The majority of participants in the post-test – 59(59%) – were proficient, 30(30%) were developing and 11(11%) were expert in clinical simulation among nursing students. The respondents distribution based on how satisfied nursing students are with clinical simulation. Of the participants in the pre-test, 44(44%) were satisfied and 56(56%) were not. Four (4%) participants were not pleased with the post-test, whereas the majority of 96(96%) people were. Conclusion: Students reported high levels of satisfaction with the simulation experience, indicating its effectiveness in complementing traditional teaching methods. Overall, simulation serves as a critical bridge between theory and practice, supporting the development of competent, confident and patient – centered nursing professionals who are better prepared to contribute to quality healthcare and improved patient outcomes.